Study on the Usability of Bauxite Resources in the South of Chongqing - Yuan GAO; Peipei HUANG; Xuzhong ZHENG; Xiong ZHANG; Liangmei JIANG; Bo HUANG; Yong ZHANG (Kuangchan zonghe liyong, 2024)
This an article in the field of mining engineering. In order to further study the development and utilization prospects of bauxite resources in the southern region of Chongqing, this article adopts methods such as on-site investigation, questionnaire survey, and data collection. By constructing an evaluation index system for the availability of mineral resources, an evaluation model based on Analytic Hierarchy Process and Weighted Superposition Method is used to conduct in-depth research and evaluation of the availability of bauxite resources in the southern region of Chongqing. Firstly, based on the expert scoring results, select the top 12 indicators with average scores as the evaluation indicators for this evaluation. Secondly, use the Analytic Hierarchy Process to determine the weights of the 12 evaluation indicators. Finally, use the weighted superposition method to determine the evaluation indicators for each mining area. The higher the score of the evaluation index, the higher the availability of bauxite resources. Among the 15 bauxite mining areas in the southern region of Chongqing, there are no easy to use mining areas, but there are 4 available mining areas. Recently, there are 7 difficult to use mining areas, and 4 difficult to use mining areas. The evaluation model established using Analytic Hierarchy Process and Enhanced Superposition Method can provide scientific reference for the evaluation of the availability of bauxite resources.